(En) coding care into digital urbanism: Vignettes of collective practices - Niloufar Vadiati; Letizia Chiappini; Martin Bangratz (Digital Geography and Society)
The tech-entrepreneurial model behind the computation of urban processes is (re) producing what has already been identified as a technocratic, solutionist, and commodifying model of urban planning. Within this model, not only is care no longer a prerequisite for urban production, but decades of smartification and platformization have been diminishing the spaces, infrastructures, and socio-economic relations that were co-produced to enable care.Through the lens of feminist geography, care is examined as a multidimensional concept encompassing socio-spatial dynamics, power relations, and ethical urban practices. Using empirical data from three research projects, the study showcases alternative digital urbanism practices, categorized into three vignettes: refusal, commoning, and reappropriation. These categories are illustrated with cases such as grassroots food cooperatives, feminist hack-spaces, digital sovereignty initiatives, platform-based welfare experiments and civil society initiatives such as Code for Germany.By situating care within the spatial and social fabric of urban life, the paper argues for its potential as a politic, practice, and epistemology that challenges the exploitative logic of contemporary digital infrastructures. The findings reveal the embeddedness of care practices within local contexts, highlighting the dual need for trans-local networks and territorial embeddedness. This study contributes to the discourse on caring digital urbanism, advancing a feminist theorisation of everyday digital urbanism.